Active extensional faults in the central-eastern Iberian Chain, Spain - Simón, J.L.; Arlegui, L.E.; Lafuente, P.; Liesa, C.L. (Journal of Iberian Geology, 2012)
Among the conspicuous extensional structures that accommodate the onshore deformation of the Valencia Trough at the centraleastern Iberian Chain, a number of large faults show evidence of activity during Pleistocene times. At the eastern boundary of the Jiloca graben, the Concud fault has moved since mid Pliocene times at an average rate of 0.07-0.08 mm/y, while rates from 0.08 to 0.33 mm/y have been calculated using distinct stratigraphic markers of Middle to Late Pleistocene age. A total of nine paleoseisms associated to this fault have been identified between 74.5 and 15 ka BP, with interseismic periods ranging from 4 to 11 ka, estimated coseismic displacements from 0.6 to 2.7 m, and potential magnitudes close to 6.8. The other master faults of the Jiloca graben (Calamocha and Sierra Palomera faults) have also evidence of Pliocene to Late Pleistocene displacement, with average slip rates of 0.06 and 0.11-0.15 mm/y, respectively. At the eastern boundary of the Teruel graben, the Sierra del Pobo fault has been active since Late Miocene times, at slip rates of 0.06-0.11 mm/y. Quaternary activity its better constrained for the Teruel fault, which offsets two fluvial terraces, with an estimated slip rate of 0.12 mm/y since 76 ka BP. A widespread, NNE-SSW trending fault system extends over the easternmost Iberian Chain (Maestrat sector), with abundant proofs of activity during Early to Middle Pleistocene s.l. times. Nevertheless, such proofs are mainly geomorphologic, while dated stratigraphic markers allowing precise assessment of slip rates are absent.